When perfect meets aorist Aoristic resultative in languages built on descending time (Tocharian, Albanian and Slavic) (Philologia, 2021)
Because of its implicational meaning and perfective aspect, the position of the aorist resultative is quite special in languages which are built on Descending Time (Hewson & Bubenik 1997). Sometimes it functions as a perfect, sometimes as a pluperfect, and sometimes it acquires other meanings, for example conditional. It often does not form any resultative at all. This article is intended to answer the question, ”What is the position of the aoristic resultative?”, i.e. what is its relation to the perfect (auxiliary in the imperfective present) and to the pluperfect (auxiliary in the imperfective past)? In order to answer these questions, the author will analyze the taxis formation with the auxiliary in the present (imperfective present), imperfect (imperfective past) and aorist (perfective past) in three Indo-European families which are built on the representation of Descending Time, i.e. Tocharian, Albanian, and Slavic (Old Church Slavonic, Sorbian and especially Polish). By the comparative analysis it will be demonstrated that there are some semantic and formal constraints on forming the aoristic resultative in languages that are constructed on the representation of Descending Time. These constraints will explain why the aoristic resultative is an unstable category and acquires different meanings and uses.